The Effect of Golden Snail Liquid Organic Fertilizer on Growth and yield of two two red lettuce (Lactuca Sativa L) Varieties - Intan Rohma Nurmalasari; Rafika Wahyu Nita; A. Miftakhurrohmat (Nabatia, 2023)
This research was conducted in Modong Village, Tulangan District, Sidoarjo Regency and continued with further research at the Agrotechnology Laboratory of Muhammadiyah Sidoarjo University. This research will be conducted in March-June 2023. This study used the Factorial Pattern Group Random design method, namely Red Lettuce Red Rapid and Lolorosa varieties with the provision of Gold Snail POC concentrations, namely 25 ml / polybag, 50 ml / polybag, 75 ml/polybag. The data obtained was analyzed using Fingerprint Analysis (Annova) and if the real difference was continued with the 5% Honest Real Difference Test (BNJ). The variables observed were plant height, number of leaves, wet weight, dry weight, root length and harvest index. Based on the results of the study showed that the red rapid lettuce variety is a variety that has a very real influence on the observation variebel of plant height, number of leaves and wet weight, but does not have a real effect on the observation variables of root length, dry weight and harvest index. Based on the results of the study showed that the red rapid lettuce variety is a variety that has a very real influence on the observation variebel of plant height, number of leaves and wet weight, but does not have a real effect on the observation variables of root length, dry weight and harvest index. The treatment of gold snail POC with 50 ml administration had a very real effect on the observation variable of plant height at the age of 28 HST